Baseline Technetium-99m Tetrofosmin Myocardial Perfusion Study In Predicting The Management Outcome Of Patients With Newly Diagnosed Myocardial Infarction - Yaser, Siti Nooraein (2019)
Background: Thrombolytic therapy is one of the treatment modality in ST elevation myocardial infarction (STEMI) although percutaneous coronary intervention (PCI) is an established gold standard treatment. Myocardial Perfusion Study (MPS) is one of the diagnostic modalities that can be used for risk stratification post STEMI. The purpose of this research is to study the role of MPS in predicting the management outcome in newly diagnosed STEMI patients. Methods: Post STEMI with thrombolytic treatment referred for MPS were included in this study. MPS findings including semi quantitative analysis of severity of ischaemia, automated summed difference score (SDS), left ventricular ejection fraction (LVEF), end diastolic volume (EDV) and end systolic volume (ESV) were obtained. Follow up was done 12 months after baseline MPS. Primary outcome on types of management with secondary outcome were studied in relation to MPS findings. Results: Seven patients had encountered cardiac hard events 12 months after the baseline MPS. All were male with mean age of 54.3 years old. Analysis of MPS findings and primary outcome found that moderate to severe ischemia, SDS of 5 - 6 (OR = 49.875; 95% CI 11.30 – 220.16), SDS of ≥7 (OR = 39.35; 95% CI 10.51 – 147.35), and LVEF ≥35% had significant unadjusted increased chance for revascularisation. Moderate to severe ischemia (OR = 285.8; 95% CI 28.15 - 2902.08) and LVEF ≥ 35%(OR = 54.04; 95% CI 6.10 – 478.56) had significant increased chance for revascularisation when adjusted to other confounding factors in multivariate analysis. Meanwhile LVEF of 23.7% with range 17-29% (OR = 0.593; 95% CI 0.39 – 0.9), EDV of 172.6 ml with range 155-197 mls (OR = 1.13; 95% CI 1.05 – 1.21), and ESV of 130.9 ml with range 110-141 mls (OR = 1.16; 95% CI 1.03 –1.31) had significant unadjusted increased chance of cardiac hard events.